Pragmatic partnership: Russian reset versus American-German relations (Economic and Political Thought, 2017)
A reset in the relations between Washington and Bonn resulted from thereorientation in the United States’ foreign policy that took place when PresidentBarack Obama took office. It was assumed that the problems piling upin front of the new administration in connection with international involvementand the economic crisis were global in character and required cooperationwith the allies from NATO (with whom the relations were not good) aswell as Russia. President Obama hoped for cooperation with Russia, whichmany observers described as naïve and attributed to his lack of experience.The reset policy soon started to burn out and there was a gradual process ofgoing away from it. It was stopped by the Russian aggression against Ukraineand the annexation of Crimea in March 2014. The influence of the failure ofthe reset policy in the American-Russian relations on the American-Germanrelations should be analysed in the context of the two states’ policy andhopes they had in connection with their reciprocal relations. Regardless ofthe disappointment, because of the two states’ role in international relations,bilateral relations are rational and moderate in character. This concerned andalso concerns the policy toward Russia.